Dampak Pengangguran Terhadap Stabilitas Sosial Dan Perekonomian Indonesia - Siti Fatimah Azzahra; Lystiana Dewi Putri; Fachriza Yunanda Purba; Dahri Tanjung; Ajeng Rezkitaputri; Ratu Zaskia Daimatul Zulva (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The impact of unemployment is divided into two aspects seen from economic development, namely the impact of unemployment on a country's economy and the impact of unemployment on the economy of individuals who experience it and society. The aim of this journal is to determine the impacts of unemployment on Indonesia's social and economic stability. The method used is the descriptive-qualitative analysis method. The results of this journal explain that unemployment can cause consumption to decrease, because unemployment can reduce household income, which as a result can reduce consumer spending. Overall, the social impact of unemployment can be very detrimental to Indonesian society, causing economic and psychological stress for those affected. Therefore, it is important to implement policies and programs that aim to reduce unemployment rates and support people who have difficulty finding work.